Antiepidermis autoantibodies induced by anti-PD-1 therapy in metastatic melanoma. Issue 5 (October 2016) - Brunet-Possenti, Florence; Mignot, Sabine; Deschamps, Lydia; Descamps, Vincent
Abstract : Skin rashes induced by anti-PD-1s are often reported; however, their immunological profiles are currently unknown. We report the case of an atypical eruption induced by pembrolizumab, associated with the occurrence of antiepidermis autoantibodies. As the onset of lesions was concomitant with the favorable tumor response, we suggest that this hybrid rash belongs to a new category of paraneoplastic syndrome, reflecting the intense immunomodulation induced by pembrolizumab. With the increasing use of anti-PD-1s, this kind of report may become frequent. For a better understanding of immune-related adverse events, physicians should document the immunological characteristics of atypical skin toxicities. Moreover, the kinetics of induced autoantibodies could provide a proxy measure of anti-PD-1 activity after treatment disruption.